2014
DOI: 10.4161/mabs.27760
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed screening of natural humoral immunity identifies antibodies at fine specificity for complex and dynamic viral targets

Abstract: (2014) Multiplexed screening of natural humoral immunity identifies antibodies at fine specificity for complex and dynamic viral targets, mAbs, 6:2, 460-473,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…In nonrandomized clinical studies, treatment of pregnant women with hyperimmune globulin was reported to improve pregnancy outcome in several studies (34,35,38,84) with limited effect in one study (37). As novel therapeutics, human MAbs specific for epitopes on HCMV proteins have been developed using technological advancements in human B-cell cloning (51,85,86). TBPC phenotype and differentiation capacity were rescued by anti-gB MAb treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nonrandomized clinical studies, treatment of pregnant women with hyperimmune globulin was reported to improve pregnancy outcome in several studies (34,35,38,84) with limited effect in one study (37). As novel therapeutics, human MAbs specific for epitopes on HCMV proteins have been developed using technological advancements in human B-cell cloning (51,85,86). TBPC phenotype and differentiation capacity were rescued by anti-gB MAb treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We also used M23, a mouse monoclonal antibody to UL112 and -113 (49,50), and a cocktail of mouse monoclonal antibodies directed against HCMV ICPs (MAB8121 containing clones 8B1.2, 1G5.2, and 2D4.2; Millipore, Billerica, MA). TRL345, a human IgG1 monoclonal antibody (MAb) against the conserved AD-2 epitope of HCMV gB (51), and control IgG1 MAb Synagis, which is reactive with respiratory syncytial virus (52), were provided by Trellis Bioscience, LLC (Menlo Park, CA).…”
Section: Methodsmentioning
confidence: 99%
“…From 2.5 million B cells surveyed from the donor with the highest frequency of anti-AD-2 B cells, 30 MAbs were cloned by single-cell cDNA PCR and expressed in HEK293 cells. As previously described, the V H and V L germ line usage in this set of MAbs was restricted, including both published and previously unidentified gene families against this target (44). Based on its superior potency for neutralizing HCMV in vitro (44) compared to that of the other MAbs cloned in the same manner, TRL345 was chosen for further characterization.…”
Section: Screening Technologymentioning
confidence: 99%
“…As previously described, a total of 15 CDR residues were somatically mutated in TRL345, with 4 in the light chain and 11 in the heavy chain (44). None of these introduced new stability risks (such as deamidation, glycosylation, acidic cleavage, isomerization, or oxidation motifs) (66).…”
Section: Screening Technologymentioning
confidence: 99%
See 1 more Smart Citation